Illocutionary Act of Printed Cigarette Advertisement Issued in TIME Magazine from 1990-2000 - Hary Prasojo Syafa'atillah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The governments all over the world have stricken the advertising of cigarettes in any media in order to discourage people from smoking and improve public health, including the printed ones in magazines. Consequently, the advertiser has also come up with a strategy so that cigarettes can be advertised and accepted without violating the government regulation. This research aims to find the hidden meaning of the advertisement through the use of illocutions contained in the printed cigarette advertisements collected from the TIME magazine issued between 1990-2000. The result shows that there are illocutions found in 29 printed advertisements such as 10 direct-literal illocutions, 7 direct-non-literal illocutions, and 12 indirect-non-literal illocutions.Â